2022
DOI: 10.1177/22808000221136483
|View full text |Cite
|
Sign up to set email alerts
|

Thermal investigation and physiochemical interaction of H2O and C2H6O2 saturated by Al2O3 and γAl2O3 nanomaterials

Abstract: Applications: The interaction of nanoparticles and base solvents of different nature attained much interest of the researchers in the recent time. These use in medication, detection of cancer cells, applied thermal engineering, and electrical and mechanical engineering. Among the broad range of applications, investigation of nanofluid through converging/diverging channel is important which is of much interest in the field of medical sciences. Purpose and methodology: The core purpose of this study is to introd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…where 𝜁 is the solid volume fraction of nanoparticles and γAO indicates aluminum oxide nanoparticles, "W" stands for water and "EG" is ethylene glycol [44]. Dynamic viscosity…”
Section: Nanofluids Thermophysical Attributes and Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…where 𝜁 is the solid volume fraction of nanoparticles and γAO indicates aluminum oxide nanoparticles, "W" stands for water and "EG" is ethylene glycol [44]. Dynamic viscosity…”
Section: Nanofluids Thermophysical Attributes and Modelsmentioning
confidence: 99%
“…ρnfbadbreak=()1ζρfgoodbreak+ζρs,ρCpnfgoodbreak=()1ζρCpfgoodbreak+ζρCps,$$\begin{equation*} {\rho }_{nf} = \left( {1 - \zeta } \right) {\rho }_f + \zeta {\rho }_s, {\left( {\rho {C}_p} \right)}_{nf} = \left( {1 - \zeta } \right) {\left( {\rho {C}_p} \right)}_f + \zeta {\left( {\rho {C}_p} \right)}_s,\end{equation*}$$ ρβnfbadbreak=()1ζρβfgoodbreak+ζρβs$$\begin{equation}{\left( {\rho \beta } \right)}_{nf} = \left( {1 - \zeta } \right) {\left( {\rho \beta } \right)}_f + \zeta {\left( {\rho \beta } \right)}_s\end{equation}$$where ζ$\zeta $ is the solid volume fraction of nanoparticles and γAO indicates aluminum oxide nanoparticles, “ W ” stands for water and “ EG ” is ethylene glycol [44].…”
Section: Model Developmentmentioning
confidence: 99%
“…In 2022, Indumathi et al examined a hybrid nanofluid with a permeable surface under the suction and injection process. The results of the physical model showed that increasing the number of nanoparticles in the basic fluid will result in a decrease in the velocity of hybrid nanofluids. In 2022, Mburu et al investigated the unsteady, two-dimensional, viscous, and incompressible flow of the boundary layer of an electrically conducting nanofluid through porous plates. Bivariate spectral quasilinearization (BSQL) was used for the model study.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, using TiO 2 particles yielded the highest energy conversion efficiency (35.67%). Alharbi et al 28 30 created a nanofluid model with TiO 2 in the base fluid within a squeezing/dilating channel, which included nanoparticle accumulation effects and nonlinear thermal radiations. The outcome confirmed that the fluid mobility is substantially controlled by the high viscosity variation caused by nanomaterials aggregation.…”
Section: Introductionmentioning
confidence: 99%